2020
DOI: 10.1177/1756287220916614
|View full text |Cite
|
Sign up to set email alerts
|

Frailty assessment in older urological patients prior to surgery: a systematic review and narrative synthesis

Abstract: Background: Radical cystectomy (RC) and urinary diversion are the recommended treatment for patients with muscle invasive bladder cancer. This is complex surgery, associated with significant patient morbidity and mortality. Frailty has been shown to be an independent risk factor for adverse outcomes in several surgical populations. Preoperative assessment of frailty is advocated in current guidelines but is not yet standard clinical practice. Aims: This systematic review and narrative synthesis aims to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Frailty will be identified as CFS≥5, rEFS≥8 and eFI≥0.25 27 52 53. The choice of frailty tools aims to first, accurately measure frailty in this sample and second, describe the routine usage of different frailty tools across the four nations of the UK 52–58…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty will be identified as CFS≥5, rEFS≥8 and eFI≥0.25 27 52 53. The choice of frailty tools aims to first, accurately measure frailty in this sample and second, describe the routine usage of different frailty tools across the four nations of the UK 52–58…”
Section: Methodsmentioning
confidence: 99%
“…27 52 53 The choice of frailty tools aims to first, accurately measure frailty in this sample and second, describe the routine usage of different frailty tools across the four nations of the UK. [52][53][54][55][56][57][58] Process of care data will be recorded regarding the nature of preoperative assessment, anaesthesia type, catheterisation and postoperative care level.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…The comorbidity burden (evaluated with the Charlson Comorbidity Index or the American Society of Anesthesiology (ASA) score, for example) is also associated with higher morbidity and mortality rates following RC [ 7 ]. Furthermore, several studies have shown that frailty (measured with various tools, such as the modified frailty index (mFI)), is an independent risk factor for adverse events following RC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%